IFRS recognition: intellectual capital in the context of higher education institutions (Revista "Boletín el Conuco", 2022)
With the arrival of globalization new concepts emerged, one of them is intellectual capital, defined as an intangible asset that is responsible for adding value to the company through criteria such as research, innovation and development, through knowledge that are acquired in the activities of a company or association. On the other hand, being a source of intangibles, universities are considered as social enterprises, especially because they make up a set of information, services, goods, among others, in search of greater community benefits. For this reason, the scope of this research focuses on contributing to a process of recognition of intellectual capital under IFRS regulations within the higher education institutions of the city of Villavicencio. For the purposes of this research, information collection instruments, characterization sheet, interviews and surveys applied to the analysis unit were incorporated, all with the purpose of achieving a harmonious development around the problem posed, mainly in search of integration. of accounting concepts with the development of intellectual capital in university training spaces.
Keywords: structural capital; human capital, intellectual capital; relational capital; recognition